2013
DOI: 10.1021/cs300781v
|View full text |Cite
|
Sign up to set email alerts
|

Selective Dehydration of Alkanediols into Unsaturated Alcohols over Rare Earth Oxide Catalysts

Abstract: Syntheses of unsaturated alcohols in the vaporphase catalytic dehydration of alkanediols over rare earth oxides are reviewed. CeO 2 effectively catalyzes the dehydration of 1,3-butanediol to produce 3-buten-2-ol and trans-2-buten-1ol. Heavy rare earth oxides such as Er 2 O 3 , Yb 2 O 3 , and Lu 2 O 3 selectively catalyze the dehydration of 1,4-butanediol to produce 3-buten-1-ol. In the dehydration of 1,5-pentanediol, Yb 2 O 3 , Lu 2 O 3 , and Sc 0.5 Yb 1.5 O 3 catalysts efficiently work to produce 4-penten-1-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
79
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 73 publications
1
79
1
Order By: Relevance
“…In our previous work, we found that REO with small ionic diameter of rare earth metal cation is effective in the formation of unsaturated alcohols from diols. 13 In the present work, the highest formation rate of 3B2OL was obtained at the smallest ionic radius of Sc 3+ , although the rate for Sc 2 O 3 at 325°C was underestimated due to the high conversion. This indicates that an active site may generate on surface adsorption sites of a compact size over Sc 2 O 3 catalyst.…”
contrasting
confidence: 38%
See 2 more Smart Citations
“…In our previous work, we found that REO with small ionic diameter of rare earth metal cation is effective in the formation of unsaturated alcohols from diols. 13 In the present work, the highest formation rate of 3B2OL was obtained at the smallest ionic radius of Sc 3+ , although the rate for Sc 2 O 3 at 325°C was underestimated due to the high conversion. This indicates that an active site may generate on surface adsorption sites of a compact size over Sc 2 O 3 catalyst.…”
contrasting
confidence: 38%
“…13 Catalytic activity of REOs depends on the position of OH groups of reactant diols: 1,3-diols are effectively dehydrated into 3B2OL and 2-buten-1-ol by CeO 2 ; 1,4-butanediol can be dehydrated to 3-buten-1-ol by Er 2 O 3 , Yb 2 O 3 , and Lu 2 O 3 ; 13 1,5-pentanediol to 4-penten-1-ol by Sc 0.5 Yb 1.5 O 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…111,114 Dehydration of 1,3-BDO into UOLs such as 3B1OL, 2B1OL, and 3B2OL have been investigated over ZrO 2 , 81 solid acid metal oxides, 81 CeO 2 -ZrO 2 , 115 and all of the rare earth metal oxide catalysts. 116,117 In the rare earth oxides, CeO 2 is the most active and selective catalyst. CeO 2 with weak basic sites shows the highest 1,3-BDO conversion at 325°C as well as the sum of selectivity of 2B1OL and 3B2OL over 99%.…”
Section: Dehydration Of 13-bdo Into Uolsmentioning
confidence: 99%
“…The catalytic activity is Changes in the formation rate of the total corresponding UOLs with ionic radius of rare earth cations. 96,117 strongly dependent on the calcination temperature of the catalyst. In particular, the sample calcined at 800°C gave the highest 2,3-BDO conversion and 3B2OL selectivity.…”
mentioning
confidence: 99%